Analisis Kaidah Kebahasaan dalam Buku Teks Bahasa Indonesia SMP - Lisnawati, Iis; Kartadireja, Welly Nores; Rosiana, Shinta; Nurjamilah, Ai Siti (STKIP Singkawang, 2024)
This research aims to describe the suitability of texts, especially linguistic rules, contained in textbooks with the criteria for selecting teaching materials. The method used in this research is a qualitative descriptive method with library study research techniques and discourse analysis techniques. The object analyzed is the linguistic rules in the 2017 Revised Edition of the Indonesian language textbook published by the Ministry of Education and Culture for classes VII, VIII and IX at junior high school level. The results of the research show that the linguistic rules contained in the textbook are in accordance with the criteria for selecting teaching materials. In detail, the suitability of linguistic rules in course book is as follows. (1) Based on relevance criteria, the linguistic rules in course book are of very good quality level. This means that the language rules in the course book are in accordance with the language rules contained in the 2013 Curriculum Basic Competencies. (2) Based on the criteria for consistency of language rules in the course book, including a consistently good quality level. This means that the language rules contained in textbooks can reach KD in the 2013 Curriculum because they contain knowledge and skills. Knowledge in the form of linguistic theory. Skills in the form of practice or training to apply knowledge. (3) Based on the criteria for adequacy of linguistic rules in textbooks, including a good quality level. The language rules stated in the course book are sufficient to facilitate the achievement of the specified KD.